FORMULASI WHOLE BANANA (Musa paradisiaca l. L.) BISKUIT TINGGI SERAT BERPOTENSI MENCEGAH PENYAKIT DEGENERATIF PADA LANSIA - Septiani Septiani; Mia Srimiati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2020)
This research aims to analyze the effect of the substitution of the whole banana (Musa paradisiaca l.) High-fiber biscuits to prevent degenerative diseases in the elderly. This experimental research design uses a Completely randomized design (CRD) with one control formula and four substitution levels including F0 (100% wheat flour), F1 (50% wheat flour and 50% kepok banana peel flour), F2 (45% wheat flour and 55 % kepok banana peel flour), F3 (40% flour and 60% banana peel flour) and F4 (35% flour and 65% of banana peel flour). .The results of the proximate analysis of selected whole banana (musa paradisiaca l.) biscuits contain 16.64% fiber, 63.18% carbohydrate, 21.58% fat, 5.64% protein, 469.50 kcal / 100g energy, 6.49% water, and 3.11% ash. This research concludes that the control formula biscuits is significant different from the selected whole banana (musa paradisiaca l.) biscuits formula (p <0.05) in in each analysis (water, ash, fat, protein, carbohydrate, and fiber).